HUBUNGAN KUALITAS PELAYANAN ADMINISTRASI PENDAFTARAN DENGAN MINAT KUNJUNGAN ULANG PASIEN UMUM DI PUSKESMAS SIMPANG KAWAT KOTA JAMBI - restidewirahmawati_15 rahmawati; Yeyen Gustina Irawan; Listautin (LPPM Universitas Awal Bros, 2026)
The quality of registration administrative services is an important aspect of healthcare services as it represents the first point of contact between patients and healthcare facilities, which can influence patients’ intention to revisit. This study aims to determine the relationship between the quality of registration administrative services and the revisit intention of general patients at Simpang Kawat Public Health Center, Jambi City. This study used a quantitative method with a correlational analytic design and a cross-sectional approach. The study was conducted from December to January 2026 at Simpang Kawat Public Health Center, Jambi City. The population consisted of general patients who had visited at least twice, with a sample of 83 respondents selected using simple random sampling. Data were collected using questionnaires with a Likert scale for service quality variables and a Guttman scale for revisit intention. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test. The results showed that most respondents perceived the quality of registration administrative services as good. The bivariate analysis indicated that only the assurance dimension had a significant relationship with patients’ revisit intention (p < 0.05), while tangibles, reliability, responsiveness, and empathy dimensions did not show a significant relationship (p > 0,05). In conclusion, there is a relationship between the assurance dimension of service quality and patients’ revisit intention. Therefore, it is recommended that the health center improve service quality, especially in the assurance aspect, such as staff competence, effective communication, and trust and security in service delivery.